2022
DOI: 10.1111/iej.13846
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethylenediaminetetraacetic acid irrigation on the regenerative endodontic procedure in an immature rat molar model

Abstract: Aim: To analyse the influence of ethylenediaminetetraacetic acid (EDTA) on the repair process in immature rat molars after a regenerative endodontic procedure (REP). Methodology:The lower first molars of 12 4-week-old Wistar rats underwent pulpectomy in the mesial root and were divided into the following groups: sodium hypochlorite (NaOCl; n = 6) -the mesial canals were irrigated with 2.5% NaOCl for 5 min, and NaOCl-EDTA (n = 6) -the canals were irrigated with 2.5% NaOCl, followed by 17% EDTA for 5 min each. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…The data of REP‐SS corroborate with the previous results of Reis‐Prado et al. (2023), which showed that the use of EDTA in REP increased the deposition of mineralized tissue in the root. However, the REP‐F18Co group had significant greater OCN immunolabelling.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The data of REP‐SS corroborate with the previous results of Reis‐Prado et al. (2023), which showed that the use of EDTA in REP increased the deposition of mineralized tissue in the root. However, the REP‐F18Co group had significant greater OCN immunolabelling.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that the F18Co bioglass solution induced the formation of connective tissue inside the root canal, with collagen maturation, the presence of PCNA-positive cells and higher OCN immunolabelling, whilst did not influence the formation of mineralized tissue on the walls of the root canal. Wistar rat molars were used because they provide an acceptable and previously standardized model (Reis-Prado et al, 2023). These animals exhibit biological responses and repair processes, and histological characteristics similar to those of humans (Cintra et al, 2016;Dammaschke, 2010;Sasaki & Kawamata-Kido, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study, 24 conducted using an immature rat molar model, suggested that EDTA irrigation may have a detrimental effect on the regenerative process. This underscores the importance of careful consideration when employing EDTA in regenerative endodontics and highlights the need for further research to determine the optimal irrigation solution.…”
Section: Discussionmentioning
confidence: 99%